Deteksi Kemurnian Air Zamzam Menggunakan Metode Spektrofotometri Near Infra Red (NIR) dan Kemometrik (Detection of Zamzam Water Purity Using Near Infra Red Spectroscopy (NIR) and Chemometrics) - Irwin Ulil Hidayah; Bambang Kuswandi; Lestyo Wulandari (UPT Percetakan dan Penerbitan Universitas Jember, 2014)
Zamzam water is called the holy water that is located in the heard city of Mecca. Zamzam is believed to have many benefits for health so widely consumed by Moslems throughout the world. In 2010, the Government of Saudi Arabia implementing rules ban export of zamzam water for commercial purposes, but zamzam water are sold freely in the world. In this research, the determination of the purity of Zamzam water was developed. The method used was NIR spectroscopy combined with multivariate statistical methods (chemometric). Zamzam water simulation were consist of pure Zamzam water, mineral water, and a mixture of Zamzam water and mineral water with a concentration range of 0% -100%. Chemometric model used are PLS, LDA, SIMCA, and SVM. LDA classification model is the best chemometric model with 100% recognition ability and prediction ability respectively. NIR spectroscopy and chemometric method have been applied succesfully to detect the purity of Zamzam water samples which marketed in Jember. Keywords:zamzam water, purity, NIR, spectroscopy, chemometrics.